Pengembangan Booklet Keanekaragaman Jenis Lichen Di Kota Pekanbaru Sebagai Suplemen Bahan Ajar Biologi Kelas X SMA - Salsabila Rika Apriliani; Fitra Suzanti; Nursal Nursal (LPPM Institut Pendidikan Nusantara Global, 2026)
The purpose of this research is to develop a research-based booklet on Lichen Diversity in Pekanbaru City. The development method used in this research is the ADDIE development method which is limited to three stages, namely Analyze, Design, and Development. This research was conducted by developing research results into booklets about the types of lichen in Pekanbaru City. The booklet validation consisted of two lecturers from the Department of Biology Education, Riau University, who were material experts and learning media experts. The results of this study obtained an average validity score of 3.48 so this booklet is included in the very valid category and is declared feasible to be used as a teaching material supplement and used in the learning process in Class X SMA Biodiversity Material. The developed booklet serves as a practical supplementary teaching material because it presents information in a concise, structured, and visually engaging format. Clear explanations, photographs, and systematic organization allow students to independently explore learning materials beyond textbooks. Furthermore, booklet-based learning media are suitable for supporting flexible learning activities, both inside and outside the classroom, in accordance with the principles of student cantered learning promoted in the Merdeka Curriculum. The validation results demonstrate that the booklet meets pedagogical and content standards, ensuring accuracy, readability, and relevance to curriculum demands. The involvement of material experts and media experts strengthens the credibility of the developed product.